Clinical and Serologic Correlates of Anti‐PM/Scl Antibodies in Systemic Sclerosis: A Multicenter Study of 763 Patients. Issue 6 (June 2014) - D'Aoust, Julie; Hudson, Marie; Tatibouet, Solène; Wick, James; the Canadian Scleroderma Research Group; Mahler, Michael; Baron, Murray; Fritzler, Marvin J.
<x xml:space="preserve">Abstract</x> Objective Anti‐PM/Scl autoantibodies are found in polymyositis, dermatomyositis, systemic sclerosis (SSc), and systemic autoimmune disease overlap syndromes. PM‐1α is a major epitope of the PM/Scl complex, and antibodies against PM‐1α can be detected using a validated enzyme‐linked immunosorbent assay (ELISA). This study was undertaken to determine the prevalence and identify the clinical correlates of anti–PM‐1α antibodies in a large cohort of patients with SSc. Methods Serum samples were obtained from 763 patients with SSc enrolled in a multicenter Canadian cohort. The sera were analyzed by ELISA for the presence of antibodies against PM‐1α. Associations between the presence of anti–PM‐1α antibodies and demographic, clinical, and other serologic manifestations of SSc were investigated. Results Anti–PM‐1α antibodies were present in 55 patients with SSc (7.2%), of whom almost 50% (26 of 55; 3.4% of the overall cohort) had no other SSc‐specific antibodies, namely anticentromere, anti–topoisomerase I, and anti–RNA polymerase III. Features positively associated with the presence of anti–PM‐1α antibodies included younger age at disease onset, skeletal muscle involvement, calcinosis, inflammatory arthritis, and overlap disease. Interstitial lung disease was less frequent and there were fewer gastrointestinal symptoms present in patients with anti–PM‐1α antibodies compared to patients without these antibodies. Conclusion Anti–PM‐1α antibodies are relatively common in SSc and are associated with a distinct clinical phenotype, consistent with that described in association with other anti‐PM/Scl autoantibodies. Although anti–PM‐1α antibodies are not exclusive of other SSc‐specific antibodies, they can be present in the absence thereof. Thus, anti–PM‐1α antibodies may have considerable diagnostic and prognostic relevance in SSc.